2018
DOI: 10.1021/acs.jpcc.8b07398
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Catalysis on Bimetallic Surface—Selective Hydrogenation of Alkynes to Alkanes or Alkenes

Abstract: Utilization of plasmonics as a driving tool for chemical transformation triggering enables to achieve unprecedented results regarding photochemical conversion efficiency and chemical selectivity regulation. In this study, the bimetallic surface plasmon-polariton-supported grating is proposed as an effective background for plasmon-induced hydrogenation of alkynyl groups of absolute chemoselectivity. The periodical bimetallic structure consists of spatially modulated gold layers, covered with the nanometer-thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…The exact mechanism of the interaction of plasmon with organic molecules is still questionable and has been discussed extensively recent years [ 88 , 89 ]. Anyway, now we can certainly confirm that plasmonic energy significantly enhances the rate of the reaction and provides an alternative method for the activation of chemical transformations, such as Pd-catalyzed cross-coupling reactions [ 90 , 91 ], hydrogenations [ 92 , 93 , 94 ], cycloadditions [ 95 , 96 ], oxidative reactions [ 97 , 98 ].…”
Section: Plasmon Initiated Nitroxide Mediated Polymerization Pi-nmmentioning
confidence: 95%
“…The exact mechanism of the interaction of plasmon with organic molecules is still questionable and has been discussed extensively recent years [ 88 , 89 ]. Anyway, now we can certainly confirm that plasmonic energy significantly enhances the rate of the reaction and provides an alternative method for the activation of chemical transformations, such as Pd-catalyzed cross-coupling reactions [ 90 , 91 ], hydrogenations [ 92 , 93 , 94 ], cycloadditions [ 95 , 96 ], oxidative reactions [ 97 , 98 ].…”
Section: Plasmon Initiated Nitroxide Mediated Polymerization Pi-nmmentioning
confidence: 95%
“…[1][2][3][4] The combination of plasmonics and surface chemistry is an emerging research area, with a wide range of promising applications that includes sensing, photovoltaics, catalysis, imaging, and nanomedicine, among others. [5][6][7][8][9] Localized surface plasmon resonance (LSPR) in metallic nanostructures is a well established as the platform for surface enhanced Raman spectroscopy (SERS), and has seen increasing interest as a driver of highly localized surface chemistry, as described beautifully in a recent review. 10 Depending on the size and other properties of the metallic nanostructures, illumination with the resonant optical wavelength to excite LSPR modes can be used to drive surface chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, due to various disadvantages of the Lindlar catalyst (use of excess ligand and harmful Pb as a promoter), over the past decades, many catalysts have been developed based on monometallic Pd, [7][8][9][10] Au, [11][12][13] Ru, 14 Rh, 15 Ni, [16][17][18][19][20][21][22][23][24][25] Co, 26 Fe, 27 and Cu (ref. 28 and 29) as well as bimetallic Pd-Ag, 30 Pd-Au, 31 Pd-Ru, 32 Au-Pt, 33 Pd-Cu, 34 Pd-Ga, 35 Rh-Co, 36 Rh-Ni, 37 Co-Pt, 38 Ni-Cu, 39 Ni-Fe, 40,41 Cu-Fe, 41 Ni-Ga (ref. 42 and 43) and trimetallic Cu-Ni-Fe (ref.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, particularly, exploration of bimetallic nanoparticles have gained tremendous attention for the selective hydrogenation of alkynes as compared to monometallic catalysts, because they exhibit superior chemical and physical properties. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] For example, very recently Li et al have reported Pd@Au-Pd alloy surface nanocubes for semihydrogenation of alkynes to alkenes (alkene/alkane; 91/9) using a hydrogen balloon in toluene at room temperature. 31 Similarly, Lu et al also reported bimetallic Pd-Pb alloy octahedral nanocrystal based catalysts for the semihydrogenation of alkynes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation